FORMULASI FLAKES TEPUNG MOCAF (Modified Cassava Flour) DAN TEPUNG UBI JALAR KUNING (Ipomoea batatas L.) SEBAGAI ALTERNATIF SARAPAN PENDERITA DIABETES MELLITUS - wati, Rachma; Mardhatillah; hadi, abdul; andriani (Poltekkes Kemenkes Bengkulu, 2025)
Diabetes mellitus (DM) is a global health problem with increasing prevalence in Indonesia. Dietary regulation based on glycemic index (GI) is an important strategy. Mocaf flour and yellow sweet potato which have medium GI and high fiber have the potential as functional food ingredients. This study aims to develop low-glycemic flakes as an alternative healthy breakfast for people with DM. The study was conducted experimentally with a Completely Randomized Design (CRD), 3 treatments and 3 replications. Data were analyzed using ANOVA and Duncan's further test. The results showed that the treatment had a significant effect on color and taste, but not on aroma and texture. The best formulation was 70% mocaf: 30% yellow sweet potato. The results of the proximate test showed that the protein and carbohydrate levels met SNI standards. It was concluded that the addition of flour had a significant effect on color, taste, and nutritional content (P <0.05). Keywords: Flakes, Mocaf Flour, Yellow Sweet Potato Flour, Organoleptic Test, Chemical Test.